Doing Digital Migration Studies: Theories and Practices of the Everyday (Media, Culture and Communication in Migrant Societies, 2024)
Doing Digital Migration present a comprehensive entry point to the variety of theoretical debates, methodological interventions, political discussions and ethical debates around migrant forms of belonging as articulated through digital practices.,Digital technologies impact upon everyday migrant lives, while vice versa migrants play a key role in technological developments, be it when negotiating the communicative affordances of platforms and devices, as consumers of particular commercial services such as sending remittances, as platform gig workers or test cases for new advanced surveillance technologies. With its international scope, this anthology invites scholars to pluralize understandings of 'the migrant' and 'the digital'. The anthology is organized in five different sections: Creative Practices; Digital Diasporas and Placemaking; Affect and Belonging; Visuality and digital media and Datafication, Infrastructuring, and Securitization. These sections are dedicated to emerging key topics and debates in digital migration studies, and sections are each introduced by international experts. I. The emphasis on reflective ‘doing’ of digital migration studies. So far scholarship in this interdisciplinary focus area has remained relatively silent on the topic of accountability and questions of decision making in the research process. II. The truly transdisciplinary and international scope of the volume distinguishes this volume from the disciplinary oriented special issues and monographs published in the field of media and communication, anthropology, migration studies and refugee studies. Digital migration creates new challenges for cross-disciplinary dialogues that require an integration of ethnography with digital methods and critical data studies in order to look at the formation of identity and experience, representation, community building, and creating spaces of belongingness. III. The innovative emphasis on everyday lived experiences and practices sheds much needed light on the ways in which increasingly documented infrastructures of datafication and digitization are lived, negotiated and contested. For this purpose, the volume pays particular attention to the everyday use of digital media for the support of transnational lives, emotional bonds and cosmopolitan affiliations, focusing also on the role technologies such as social media and smartphones play in shaping local/urban and national diasporic formations. This is because it becomes increasingly important to give everyday digital media usage a central role in investigations of transnational belonging, digital intimacy, diasporic community (re)production, migrant subject formation, long-distance political participation, urban social integration and local/national self-organization.